2019
DOI: 10.1158/1078-0432.ccr-19-1335
|View full text |Cite
|
Sign up to set email alerts
|

Guadecitabine Plus Ipilimumab in Unresectable Melanoma: The NIBIT-M4 Clinical Trial

Abstract: Purpose: The immunomodulatory activity of DNA hypomethylating agents (DHAs) suggests they may improve the effectiveness of cancer immunotherapies. The phase Ib NIBIT-M4 trial tested this hypothesis using the next-generation DHA guadecitabine combined with ipilimumab. Patients and Methods: Patients with unresectable stage III/IV melanoma received escalating doses of guadecitabine 30, 45, or 60 mg/m 2 /day subcutaneously on days 1 to 5 every 3 weeks, and ipilimumab 3 mg/kg intravenously on day 1 every 3 weeks, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 43 publications
0
78
0
Order By: Relevance
“…Indeed, increased TE expression and de novo presentation of TE-derived peptides on MHC class I molecules were found upon treatment of cancer cells with a demethylation agent, indicating that therapeutic reactivation of tumor-specific TEs may synergize with immunotherapy. In line with this assumption, the phase IbNIBIT-M4 trial reported that treatment of patients with advanced melanoma using the next-generation DNA hypomethylating agent guadecitabine combined with ipilimumab is safe and tolerable, and shows promising immunomodulatory and antitumor activity [71].However, in an open-label phase II multicohort study administration of the oral DNA hypomethylating agent CC-486 combined with durvalumab did not demonstrate robust pharmacodynamic or clinical activity in selected immunologically cold solid tumors consisting of PD-(L)1 inhibitor naïve patients with either advanced microsatellite stable colorectal cancer, platinum resistant ovarian cancer, or estrogen receptor positive, HER2 negative breast cancer [72].…”
Section: Immune-related Mutational and Epigenetic Landscapesmentioning
confidence: 91%
“…Indeed, increased TE expression and de novo presentation of TE-derived peptides on MHC class I molecules were found upon treatment of cancer cells with a demethylation agent, indicating that therapeutic reactivation of tumor-specific TEs may synergize with immunotherapy. In line with this assumption, the phase IbNIBIT-M4 trial reported that treatment of patients with advanced melanoma using the next-generation DNA hypomethylating agent guadecitabine combined with ipilimumab is safe and tolerable, and shows promising immunomodulatory and antitumor activity [71].However, in an open-label phase II multicohort study administration of the oral DNA hypomethylating agent CC-486 combined with durvalumab did not demonstrate robust pharmacodynamic or clinical activity in selected immunologically cold solid tumors consisting of PD-(L)1 inhibitor naïve patients with either advanced microsatellite stable colorectal cancer, platinum resistant ovarian cancer, or estrogen receptor positive, HER2 negative breast cancer [72].…”
Section: Immune-related Mutational and Epigenetic Landscapesmentioning
confidence: 91%
“…T cell receptor (TCR) repertoire clonality of responders was found to be increased during therapy (36,131). In a trial combining CTLA-4 blockade with an demethylating agent, an increase in CD8+ T cell and PD-1 expression was reported (132).…”
Section: Evolution Of the Tme During Treatment And Responsementioning
confidence: 99%
“…Next-generation DHAs, however, demonstrated promising immune-modulatory and anti-tumor activity in clinical trials [56]. In this continuously evolving scenario, the phase 1b NIBIT-M4 study recently confirmed the tolerability and safety of guadecitabine associated with ipilimumab in unresectable stage III/IV melanoma, which shows a unique objective response rate of 26% [108].…”
Section: Clinical Applications Of Extracellular Vesicles and Melanomamentioning
confidence: 99%